GEOMORPHOLOGY OF CISEWU AREA AND ITS SURROUNDINGS, GARUT REGENCY, WEST JAVA, INDONESIA - Zulfi, Damar Sayyidina; Sukiyah, Emi (Universitas Padjadjaran, 2026)
This study analyzes the geomorphological phenomena of the Cisewu area and its surroundings, Garut Regency, West Java, through an integrated approach encompassing morphographic, morphometric, morphogenetic, and morphotectonic was used to analyze landforms as a basis for establishing geomorphological units. The methods used included mapping the earth's surface, Digital Elevation Model (DEM) analysis, slope gradient measurement, drainage pattern interpretation, and lineament analysis. The results identify five main geomorphological units, namely: (1) Andesite Intrusive Dome, (2) Very Steep Structural Valley, (3) Moderately Steep Volcanic Valley, (4) Steep Volcanic Ridge, and (5) Very Steep Structural Ridge. Morphometric analysis shows the dominance of steep (16°–35°) to very steep (>35°) slopes, reflecting strong control by geological structures and resistant lithology. Rectangular and trellis drainage patterns indicate control by fault and joint structures. Morphotectonic analysis using geomorphic indices (Bs, Vf, Af, Smf) indicates ongoing Quaternary tectonic activity, particularly in the Cilayu Sub-Watershed. The formation of these geomorphological units is the result of the interaction between volcanism during the Late Miocene–Pliocene and tectonic deformation by northeast–southwest-trending strike-slip faults. The results of this study provide a scientific basis for land-use planning and landslide hazard mitigation in the study area.